1984
DOI: 10.1210/endo-114-6-2301
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulatory Control of Thyrotropin in Rabbits

Abstract: Studies were designed to determine whether an autoregulation system exists for TSH in the rabbit. For this purpose, a species-specific RIA for rabbit TSH that does not cross-react with human (h) TSH was developed. Hypothyroid animals were studied at varying time periods up to 3 months after either surgical thyroidectomy or propylthiouracil (PTU) treatment. Highly purified hTSH was injected iv at doses of 0 (saline control), 0.1, 0.3, 1,3, and 10 micrograms into unanesthetized rabbits bearing chronically implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…A similar constellation was described in patients with both familiar [39] and sporadic [40] activating TSH receptor mutations and in an infant born to a mother with Graves' disease [41]. This and the fact that ultrashort loop feedback control of thyrotropin secretion had been observed in rabbits [42, 43] led to the discovery of TSH receptors on folliculostellate cells of anterior pituitary lobe [44–46] and consecutive confirmation of a similar autocrine or paracrine effect in humans [47, 48]. This feedback loop might prevent excessively high TSH levels and also be a source of TSH pulsatility, as suggested by investigations based on fractal geometry [49].…”
Section: Physiology Of Thyrotropic Feedback Controlsupporting
confidence: 54%
“…A similar constellation was described in patients with both familiar [39] and sporadic [40] activating TSH receptor mutations and in an infant born to a mother with Graves' disease [41]. This and the fact that ultrashort loop feedback control of thyrotropin secretion had been observed in rabbits [42, 43] led to the discovery of TSH receptors on folliculostellate cells of anterior pituitary lobe [44–46] and consecutive confirmation of a similar autocrine or paracrine effect in humans [47, 48]. This feedback loop might prevent excessively high TSH levels and also be a source of TSH pulsatility, as suggested by investigations based on fractal geometry [49].…”
Section: Physiology Of Thyrotropic Feedback Controlsupporting
confidence: 54%
“…Stimulation of TSH release by AVP was modest in static incubation when compared with the peaks of release elicited by AVP perifusion. It is possible that accumulation ofTSH in static incubation media may exert a local feedback on TSH secretion at the pituitary level (23). The successive removal of released TSH during perifusion circumvents this problem and could account for the higher levels of secretion.…”
Section: Utes Perifused Cells Werementioning
confidence: 99%
“…The existence of TSH autoregulation has been demonstrated by rabbit studies of hypothyroidism, using speciesspecific assay for rabbit TSH. These studies showed a fall in rabbit TSH levels when human TSH was injected [3]. After prolonged hypothyroidism this fall could not be demonstrated, indicating a possible loss of autoregulation in this circumstance.…”
Section: Introductionmentioning
confidence: 89%
“…After prolonged hypothyroidism this fall could not be demonstrated, indicating a possible loss of autoregulation in this circumstance. Autoregulation was found to be a sensitive system such that the suppression of rabbit TSH was of the same order as the rise in human TSH levels [3]. Autoregulation was active with changes to human TSH levels [3] corresponding to physiological levels.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation